Murder games - Patterson, James, 1947-; Roughan, Howard (2017)
Searching for a serial killer who leaves playing cards at the scenes of his crimes, police officer Elizabeth Needham teams up with brilliant professor Dylan Reinhart, whose book has been connected to the murders
Keywords: Policewomen -- New York (State) -- New York -- Fiction; College teachers -- New York (State) -- New York -- Fiction; Serial murder investigation -- Fiction; New York (N.Y.) -- Fiction; Fiction; Suspense fiction; Thrillers (Fiction); Detective and mystery fiction